North Atlantic tropical cyclones: a kinetic energy perspective - Fritz, Angela Marcelun (Georgia Institute of Technology, 2009)
Towards advancing the indices of hurricane energetics that are associated with potential damage, we develop a new methodology for calculating integrated kinetic energy (IKE) climatology. A simple, observation and dynamical - based radial wind speed model is used with the Extended Best Track Data Set to calculate IKE for North Atlantic Hurricanes from 1988 to 2008. The method is evaluated against previous methods of tropical cyclone intensity analysis, and the results are compared to traditional indices in terms of characterizing storm energetics and relating to storm surge. It is shown that the traditional indices are inaccurate measurements of hurricane energetics, and the assumptions that they are based on are not valid. Furthermore, in analyzing storm surge, it is possible that tropical cyclone damage is more strongly correlated with IKE rather than maximum wind speed. M.S.